Investigating inflation and the dynamics of the revenue system of municipalities (case study: Isfahan Municipality) - Nasrin Karimi (اقتصاد شهری, 2023)
Municipal taxes are one of the main sources of revenue of municipalities, which includes a large part of the revenue. Each municipality needs an efficient system of revenue collection to perform its local tasks and meet the growing urban needs, which can be adjusted for fluctuating factors and outward shocks. One of the factors affecting the real revenues of municipalities is inflation, which, depending on the case, causes a decrease or increase in revenues. On the other hand, delaying the payment of taxes by the payers is one of the factors that cause income fluctuations; therefore, in the present study, in the form of a Tanzi model of the dynamics of the Municipal Income System, the relationship between inflation and real income is examined through the calculation of the length of lags in the collection of taxes and income elasticities for the municipality of Isfahan. The data used in seasonal time series ranges from the third quarter of 1385 to the second quarter of 1400, and the method used in this study is the ARDL model. The results indicate that the duration of the lag of the collection of complications was about 4 months and the income elasticity was 41/0, and the revenues were adjusted by a change of one percent in inflation to only 41/0. So, inflation has reduced the real revenues of the municipality, and the performance of the municipality in adjusting the revenues to inflation has been ineffective. JEL Classification: R51, E31, H20.